BETWEEN POLICY AND PRACTICE: THE PERSISTENCE OF THRIFT MARKETS UNDER INDONESIA’S SECOND-HAND CLOTHING IMPORT BAN - Jufri, Nurul Fadhilah; Alamsyah, Anggriani (UIN Alauddin Makassar, 2025)
Since the mid-2010s, Indonesia has implemented a strict prohibition on the importation of second-hand clothing with the stated objectives of protecting domestic industries, safeguarding public health, and ensuring trade compliance. The aim of this study is to investigate the persistence of urban thrift markets in Makassar despite this prohibition and to examine the dynamics that shape the policy practice gap. Adopting a qualitative research design, the study draws on semi structured interviews, direct observations, and documentary analysis involving municipal officials, traders, and consumers. The findings reveal that enforcement at the local level is undermined by limited institutional capacity, corruption, and socioeconomic pressures. Despite repeated enforcement actions, informal thrift markets demonstrate structural adaptability, strong community networks, and rational strategies that sustain operations. Consumers are driven by affordability, cultural identity, and sustainability values, while traders rely on rational cost benefit calculations and social legitimacy to mitigate risks. These insights highlight that prohibition alone cannot dismantle practices deeply rooted in economic necessity and cultural consumption. The study contributes to urban political economy scholarship by integrating policy implementation theory with rational choice analysis to explain why regulatory outcomes diverge from intentions. The findings imply that effective governance of informal markets requires adaptive strategies that combine regulation, empowerment, and social protection, rather than coercive prohibition.